EFEK PENAMBAHAN UMBI BUNGA DAHLIA SEBAGAI SUMBER INULIN TERHADAP KECERNAAN PROTEIN DAN PRODUKTIVITAS AYAM LOKAL PERSILANGAN (Effect of Dahlia Tuber supplementation as Inulin Source on Protein Digestibility and Productivity of Crossbred Local Chicken) - Fanani, Anhar Faisal; Suthama, Nyoman; Sukamto, Bambang (Jurnal Kedokteran Hewan, 2016)
The research was aimed to evaluate feeding effect of powder and extract of dahlia tuber as a sources of inulin prebiotic on protein digestibility and productivity of crossbred local chicken. A total of 280 unsex local crossbred chicken with the age of 22 days and average weight of 180.461.21 g was assigned in a completely randomized design with 7 treatments and 4 replications (10 birds each). Dietary treatments consist of T0 (basal ration), T1 (T0 + 0.4% dahlia powder), T2 (T0 + 0.8% dahlia powder), T3 (T0 + 1.2% dahlia powder), T4 (T0 + 0.39% dahlia extract), T5 (T0 + 0.78% dahlia extract), T6 (T0 + 1.17% extract dahlia). Treatment was conducted for 8 consecutive weeks. Variables observed were protein digestibility, short chain fatty acid (SCFA), muscle protein mass, muscle calsium mass, and body weight. The data were analyzed using ANOVA and followed by Duncan test at the level of 5%. The results showed that feeding inulin in the form of powder or extract of dahlia tuber significantly (P0.05) increased protein digestibility, SCFA level, and body weight. Treatments T2 until T6 significantly (P0.05) increased muscle calsium mass but did not increase muscle protein mass. In conclusion, the used of 1.2% dahlia powder and 1.17% extract dahlia tuber as an inulin source increase protein digestibility and productivity of crossbred local chicken.Key words: inulin, dahlia tuber, crossbred local chicken